Effect of Acupressure on Stress and Anxiety of Patients with Multiple Sclerosis: A Sham-controlled Randomized Clinical Trial - Mohammad Ali Nahayati; Seyed Abolfazl Vaghar Seyyedin; Hamid Reza Bahrami-Taghanki; Zahra Rezaee; Nasim Mehrpooya; Hossein Rahimi (Complementary Medicine Journal of Faculty of Nursing and Midwifery, 2020)
Objective: Stress and anxiety are common in patients with Multiple Sclerosis (MS). These complications exacerbate the symptoms of MS. This study aims to evaluate the effect of acupressure on stress and anxiety of MS patients. Methods: In this randomized clinical trial, participants were 106 MS Patients referred to Multiple Sclerosis Society in Mashhad, Iran. After signing an informed consent form, they completed a demographic form and stress, and the Depression Anxiety Stress Scale - 42 items (DASS-42). Then, they were randomly assigned into intervention and sham groups by tossing a coin. Participants in the intervention group were asked apply a pressure on the Shenmen and Yin Tang acupoints for one month (once per day for 15 minutes), while the sham group applied pressure 2.5 cm below the Shenmen acupoint and 3 cm above the Yin Tang acupoint. Participants in each group were then completed the DASS-42 again one hour after the final session. Data were analyzed using chi-square test, Kolmogorov-Smirnov test, independent t-test, and Paired t-test. Results: In the intervention and sham groups, there was no statistically significant difference between the mean pre-test scores of stress (34.73±5.80 vs. 33.06±6.42) and anxiety (27.09±6.99 vs. 25.31±6.88), and neither between the mean post-test scores of stress (29.20±6.21 vs. 33.73±9.44) and anxiety (22.79±5.68 vs. 25.21±6.72) (P>0.05). However, comparison of DASS-42 scores between groups showed that the mean scores of stress and anxiety in the intervention group were significantly lower than in the sham group (P< 0.05). Conclusion: It seems that acupressure can be used along with other therapeutic and pharmacological interventions to reduce stress and anxiety in patients with MS.